Architectures of illusion: from motion pictures to navigable interactive environments. - Thomas, Maureen; Thomas, Maureen; Penz, François (NBN International, 2003)
The world of media production is in a state of rapid transformation. In this age of the Internet, interactivity and digital broadcasting, do traditional standards of quality apply or must we identify and implement new criteria? This profile of the work of the Cambridge University Moving Image Studio (CUMIS), presents a strong argument that new developments in digital media are absolutely dependent on an understanding of traditional excellence. The book stands alone in placing equal emphasis on theoretical and practical aspects of its subject matter and avoids jargon so as to be easily understood by the general reader as well as the specialist. Chapters discuss: • animation • navigable architectural environments • moving image narrativity • questions of truth and representation • virtuality/reality • synthetic imaging • interactivity This broad analysis of current research, teaching and media production contains essential information for all those working or studying in the areas of multimedia, architecture, film and television. The book is designed as a core text for the Cambridge University 1 year MPhil Degree in Architecture and the Moving Image.